Fishing Season Estimation of Mackerel Scad (Decapterus spp) with purse seines in the Sulawes Sea based on catch data - Ginting, Jebry Yanta; Pamikiran, Revols D. Ch.; Masengi, Kawilarag W. A; Luasunaung, Alfret; Dien, Heffry V.; Manu, Lusia (Jurnal Ilmiah Platax, 2022)
This study aims to determine the pattern or fluctuations in the fishing season of mackerel scad (Decapterus spp) and suspected months of the fishing season. Data analysis is made in the form of cross-tabulation and mapped into graphs. Fishing season is determined by the average percentage methods based on time series analysis. The results indicated that the fishing season of mackerel scad in the Sulawesi Sea fluctuates. The fishing season occurs from May to November with the highest season/seasonal index occurring in July, while non-seasonal conditions occur from December to April with the smallest seasonal index/non-seasonal peak occurring in January.Keywords:  mackerel scads, fishing season, fluctuation, Sulawesi SeaAbstrakPenelitian ini bertujuan untuk mengetahui mengetahui pola atau bentuk fluktuasi musim  penangkapan  dan pada bulan apa saja diduga menjadi kondisi musim penangkapan ikan layang (Decapterus spp). Penyajian dan analisis data dibuat dalam bentuk tabulasi silang dan dipetakan dalam bentuk grafik. Untuk analisis musim penangkapan ikan menggunakan Metode Presentasi Rata-rata (The Average Percentage Methodes) yang didasarkan pada Analisis Runtun Waktu (Time Series Analysis). Hasil analisis menunjukan bahwa musim penangkapan ikan layang (Decapterus spp) di Laut Sulawesi berfluktuasi. Musim penangkapan terjadi pada Mei sampai November dengan puncak musim/indeks musim tertinggi terjadi pada Juli sedangkan kondisi bukan musim terjadi pada Desember sampai April dengan indeks musim terkecil/puncak bukan musim terjadi pada Januari. Kata-kata Kunci: ikan layang, musim penangkapan, fluktuasi, laut Sulawesi.